Strategic plan of action for the prevention and control of chronic non-communicable diseases (NCDs) for countries of the Caribbean Community (CARICOM) 2010-2014 (Caribbean Community Secretariat & PAHO/WHO GeorgetownGY, 2010)
Presents a plan of action and resource mobilisation at both the regional and country levels for the prevention and control of chronic non-communicable diseases (NCDs) for countries of the Caribbean Community.
Documentation Centre has: 2010-2014; 2011-2015